Deterioration of composite restorations in tooth wear patients: translational approach. (2022) - Lima, V.P.; Crins, L.A.M.J.; Bronkhorst, E.M.; Opdam, N.J.M.; Ruben, Jan L.; Huysmans, Marie-Charlotte D.N.J.M.; Loomans, Bas A.C.; Moraes, R.R.
Abstract : Purpose/Aim: This study investigated the clinical deterioration of anterior resin composite restorations placed in tooth wear patients after 36 months and later compared the ability of two chewing simulation devices in emulating in vitro the clinical deterioration observed in those restorations. Materials and Methods: For the clinical observation, 270 anterior maxillary resin composite restorations in 47 patients were evaluated after 36 months of clinical service by using intraoral photographs and 3D scans to rate modified FDI scores and investigate the presence of degradation features. Multivariable logistic regression models were used to analyze the clinical data (p<0.05). For the in vitro approach, tooth wear was simulated in bovine incisors, which were restored with materials and techniques similar to those in the clinical observation. Incisal edges of the restorations were subjected to 960, 000 cycles of either compressive loading (Biocycle-V2; 125 N; 2 Hz) or wear and mechanical loading (Rub&Roll; 30 N; 20 rpm). Surface degradation was rated using the modified FDI scores to compare the chewing devices (Fisher's test, ?=0.05). Results: In the clinical observation, early degradation signs were present at 1 month: irregularities (41.5%) and ditching (7.4%) were observed at the surface and adhesive interfaces. The frequency of irregularities decreased in the 36-month follow up (37%), but ditching (12.2%) and fractures (10.7%) were more common. After 36 months, the most frequent esthetic deterioration was noticeable for staining (44%) and loss of luster (31%). For functional deterioration, in the 3D scans, wear (25%), marginal adaptation (24%), and surface irregularities (19%) were the most frequent forms. The simulation devices produced distinct degradation patterns: Biocycle-V2 generated deterioration not comparable to the clinical situation, including contact damage, minor wear, and localized roughening. The degradation caused by Rub&Roll was more similar to the in vivo situation, including wear facets, chipping, delamination, staining, and marginal ditching. The FDI scores differed between the chewing devices for staining, material/retention, and marginal adaptation (p?0.003). Conclusions: The clinical observation revealed a continuous deterioration process in tooth wear patients with a progression of the deterioration until 36 months. The laboratory simulation of the deterioration showed that the Rub&Roll chewing device could emulate the clinical deterioration observed in anterior restorations in tooth wear patients and could be used as a mouth simulation method, contributing to translational research.